2008
DOI: 10.4040/jkan.2008.38.5.676
|View full text |Cite
|
Sign up to set email alerts
|

Falls Risk Factors of Inpatients

Abstract: Purpose:The purpose of this study was to identify the risk factors for falls and to suggest data for developing a program for preventing falls. Methods: This was a case-control study in five university hospitals and a general hospital. In total, 216 patients over the age of 18 yr admitted from January 1 to December 31, 2007 participated. One hundred eight patients with experience of falling were matched by gender, age level, diagnosis, and length of stay with 108 patents with no experience of falling admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
18
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
5
18
0
5
Order By: Relevance
“…No previous study reported fatigue as a predictor of falls; however, a study (Kim et al. ) reported general weakness, which could be considered a symptom of fatigue, as a predictor of falls. The relationship between general weakness and fatigue should be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No previous study reported fatigue as a predictor of falls; however, a study (Kim et al. ) reported general weakness, which could be considered a symptom of fatigue, as a predictor of falls. The relationship between general weakness and fatigue should be investigated in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in South Korea, there have been domestic studies on fall risk factors only in elderly individuals and children (Cho et al. ; Kim & Lee ). Therefore, this study aimed to identify the risk factors and predictors of falls in inpatients with cancer in order to establish effective fall prevention strategies in these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…전성, 사용자 만족도를 모두 보장하는 전략을 사용하는 것이 다 (Reddy, Gill, & Rochon, 2006) (Milisen et al, 2007;Kim et al, 2008). (Brenner & Gefeller, 1997;Poses, Cebul, Collins, & Fager, 1986;Steinberg, 2009 Table 1).…”
unclassified
“…낙상의 원인은 연령, 시력, 청력 등의 감 각저하, 거동장애, 우울, 실금, 약물복용, 만성질환 등의 내재 적 요인 (Heinze, Dassen, Halfens, & Lohrmann, 2009) 과 부적절한 보행 보조기구, 신발, 조명, 미끄러운 바닥, 장애 물이 있는 환경적 요인인 외재적 요인으로 분류된다 (Kim, Lee, & Eom, 2008). 이 중 내재적 요인은 외재적 요인보다 낙상 발생에 더 강한 영향을 주는 것으로 알려져 있으며 개인 의 노력으로 조절 가능한 변수들이 있으므로 낙상 관련 연 구에서 중점적으로 다루어져 왔다 (Park, Chang, & Park, 2008).…”
unclassified